1987
DOI: 10.1111/j.1365-2362.1987.tb01147.x
|View full text |Cite
|
Sign up to set email alerts
|

Nephrotoxicity of cyclosporin A in humans: effects on glomerular filtration and tubular reabsorption rates

Abstract: The contention that cyclosporin A (CyA) nephrotoxicity may be due to renal afferent arteriolar constriction was inferred from rat studies showing CyA to increase renal vascular resistance, to reduce glomerular filtration rate (GFR) and delivery of tubular fluid from the end of the proximal tubule to the loop of Henle (Vprox), and to increase proximal fractional reabsorption. In order to test whether the mechanism of human CyA nephrotoxicity is similar to its rat analogue, and whether CyA treatment causes prolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
15
0

Year Published

1988
1988
2005
2005

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(16 citation statements)
references
References 19 publications
1
15
0
Order By: Relevance
“…Due to the contrast between the efficacy of CSA as an immunosuppressant and its high nephrotoxicity, many studies have been conducted to understand the mechanisms of CSA-induced nephrotoxicity. It has been shown that renal arteriolar constriction [4], direct fibrogenic effect on human tubulointerstitial cells [5], amplification of Ca 2+ signaling pathway [36], inhibition of COX-2 expression in response to low salt intake [37], inhibition of the adaptive responses to hypertonicity occurring during the urinary concentrating mechanism [38]and apoptosis involving mitochondrial injury [39]may contribute to CSA-induced nephrotoxicity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the contrast between the efficacy of CSA as an immunosuppressant and its high nephrotoxicity, many studies have been conducted to understand the mechanisms of CSA-induced nephrotoxicity. It has been shown that renal arteriolar constriction [4], direct fibrogenic effect on human tubulointerstitial cells [5], amplification of Ca 2+ signaling pathway [36], inhibition of COX-2 expression in response to low salt intake [37], inhibition of the adaptive responses to hypertonicity occurring during the urinary concentrating mechanism [38]and apoptosis involving mitochondrial injury [39]may contribute to CSA-induced nephrotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, treatment with CSA is limited due to its nephrotoxicity and, despite the many studies, the mechanisms underlying this harmful effect are still not understood. It has been suggested that it is due to renal arteriolar constriction, which reduces renal blood flow and glomerular filtration rate [4]. However, other studies suggested that CSA toxicity might be independent of hemodynamic alterations [5].…”
Section: Introductionmentioning
confidence: 99%
“…Chronic cyclosporin A (CyA) nephropathy is a major dose-limiting side effect of CyA therapy and is characterized by early structural and functional derangements of the proximal tubule [1, 2], extracellular matrix accumulation [3], and increased cortical expression of fibrogenic growth factors, such as transforming growth factor beta 1 (TGFβ 1 ) [4, 5], insulin-like growth factor I (IGF-I) [6, 7], and platelet-derived growth factor (PDGF) [8]. The pathogenesis of such nephrotoxicity is not fully explained.…”
Section: Introductionmentioning
confidence: 99%
“…While there is little doubt that CyA can result in acute nephrotoxicity [4,7], its ability to cause a chronic progressive loss of renal function remains questionable [5,8,10,14,171. The classic studies of Myers et al [12, 131 resulted in the widely accepted view that CyA causes a chronic and progressive loss of renal function with heart transplant patients.…”
Section: Discussionmentioning
confidence: 99%